2020
DOI: 10.3390/polym12061218
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of the Natural Polymer ε-Polylysine Against Oral Pathogens Associated with Periodontitis and Caries

Abstract: Antimicrobials are important adjuncts in the treatment of caries and periodontitis. However, increased bacterial resistance and hypersensitivity reactions to commonly used antimicrobials have led to an increasing demand for safe and natural substances. The objective of this study was to investigate the antibacterial effects of ε-polylysine against oral pathogens Streptococcus mutans and Porphyromonas gingivalis. Broth dilution assay, scanning electron microscopy (SEM) and confocal laser scanning microscopy (CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…It is therefore expected that higher PLS concentrations will be required to inhibit growth of higher inoculum concentrations. This was also demonstrated in a recent study [20].…”
Section: Antibacterial Activity and Polylysine Releasesupporting
confidence: 84%
See 2 more Smart Citations
“…It is therefore expected that higher PLS concentrations will be required to inhibit growth of higher inoculum concentrations. This was also demonstrated in a recent study [20].…”
Section: Antibacterial Activity and Polylysine Releasesupporting
confidence: 84%
“…One recent study demonstrated that polylysine had satisfactory antibacterial efficacy against S. mutans in a liquid culture medium and as an application on biofilm-dentin surfaces. The study demonstrated that the susceptibility of microorganisms to polylysine was dependent on polylysine concentrations [20]. Additionally, it showed that polylysine can kill and inhibit the growth of the periodontal pathogen Porphyromonas gingivalis [20].…”
Section: Antibacterial Activity and Polylysine Releasementioning
confidence: 99%
See 1 more Smart Citation
“…30 EPL has an efficient antimicrobial activity against several animal pathogens with a remarkable dependence on the molecular weight of the peptide. [31][32][33] Poly-L-lysine and poly-D-lysine are commercially used in promoting cell adhesion to plastic and glass surfaces.…”
Section: Polylysinementioning
confidence: 99%
“…In this article, we introduce an idea of exploiting the electroceutical properties of a marine-derived compound, namely, ε-poly-L-lysine; being positively charged [27], prepared in a nanofibrous form, in repelling the SARS-CoV-2 virus by positive-positive electrostatic interaction owing to the positively charged capsid of the virus and its newly discovered arginine motif, and hence decreasing its inhaled viral load. Moreover, we propose the incorporation of these electroceutical nanofibers as a colloidal dispersion in a nasal spray and in a toothpaste formulation, and hence uniting the electroceutical properties of the administered bioactive polypeptide with a cosmeceutical purpose.…”
Section: Introductionmentioning
confidence: 99%